Digital Work Pressure, Workplace Well-Being, and Retention Intention among Generation Z Employees: A Qualitative Study - Niken Widyastuti; Bambang Irjanto; Afnina Afnina; Yulina Astuti; Muhammad Zulkarnain (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose: This study aims to explore the experiences of Generation Z employees within digital work environments, focusing specifically on digital work pressure, workplace well-being, and retention intention. Design/methodology/approach: A qualitative approach utilizing an exploratory design and a constructivist paradigm was employed. Data were gathered through semi-structured in-depth interviews with 20 Generation Z employees working in digitally-based organizations in Yogyakarta. Participants were selected via purposive sampling, and the data were analyzed using reflexive thematic analysis. Findings/Results: The analysis identified four core themes: (1) digital work pressure as a normalized strain within digital work cultures; (2) constant connectivity and the blurring lines between work and personal life; (3) the ambivalent effects of digital work pressure on productivity and mental exhaustion; and (4) workplace well-being as an interpretive mechanism in shaping retention intention. While digital technology is perceived to enhance flexibility and productivity, continuous connectivity induces mental fatigue and challenges work-life balance. The intent to remain within an organization is evaluated through the quality of work experiences, organizational support, self-development opportunities, and work-life harmony. Originality/Value: This study enriches the literature on the digital work experiences of Generation Z and offers practical insights for organizations to design digital work policies that support employee well-being and reinforce retention.